PENGARUH KUALITAS LAYANAN DAN KELUHAN PELANGGAN TERHADAP KEPUASAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN JASA BENGKEL CV. YAMAHA YUDISTIRA PEGANDON KENDAL (Students' Journal of Economic and Management, 2014)
This study analyzed the relationship between service quality and customer complaints to the satisfaction and its impact on customer loyalty workshop services. Object of this study is the CV. Yamaha Yudistira Pegandon. Problems in the study refers to the phenomenon of decline in CV sales service. Yamaha Yudistira Pegandon significantly in December 2012, and in January, February, May, June, Septenber, October 2013. The purpose of this study was formulated to examine the factors that influence loyalty workshop services. The model is formulated in this study aims to provide a critical understanding of the concept and measurement of loyalty. Researchers incorporate elements of service quality, customer complaints and satisfaction as well as having significant consequences on loyalty workshop services. In addition to the theoretical model, this study formulates three hypotheses. Proposif sampling methods have been required to obtain the data in this study. Researchers using 100 respondents and all respondents were subscribers CV. Yamaha Yudistira Pegandon. Analysis of data using multiple regression analysis using SPSS. Yamaha Yudhisthira Pegandon. Analysis of the data using multiple regression analysis using SPSS. Quality of service has no effect on satisfaction, while the effect on the satisfaction of customer complaints and satisfaction affect customer loyalty. The final conclusion can be recommended as an insert for the management of CV. Yamaha Yudistira Pegandon. Researchers believe that the approach with regard to the dimensions of service quality, customer complaints and satisfaction can help managers improve loyalty, because these three variables important to increase customer loyalty workshop services. Keywords : Service Quality, Customer Complaints, Customer Satisfaction and Loyalty Services Workshop.